Pemberdayaan perempuan dalam penanggulangan kekerasan dalam rumah tangga di ibu-ibu Pemberdayaan Kesejahteraan Keluarga (PKK) RT 01/ RW 09 Kelurahan Air Putih Kecamatan Tampan Kota Pekanbaru - Emilda Firdaus; Sukamarriko Andrikasmi (Unri Conference Series: Community Engagement, 2019)
Domestic violence is a form of human rights violation especially against women who are always victims. The government has issued a regulation namely Law Number 23 of 2004 concerning the Elimination of Domestic Violence. But domestic violence continues. Data from the National Commission on Violence Against Women shows graphs of violence against women especially domestic violence is increasing every year. Likewise, the case of domestic violence in Pekanbaru City, Riau Province, shows quite high data. For this reason, understanding and training regarding legislation related to domestic violence are needed. The purpose of community service activities is to support higher education programs through women's studies centres to protect women's rights. Besides that, it is also to disseminate information to the public to prevent domestic violence. The method used in community service is lectures, dialogues and solving domestic violence cases, a combination of these methods is expected not only to get participants material about PKDRT but also trained to solve various problems of domestic violence. Participants in this activity are 50 PKK RT 01 / RW 09 Air Putih Village Pekanbaru City residents, with the consideration that as PKK administrators and members, they can transfer their knowledge to mothers in their neighbourhood.